Treatment target achievement after myocardial infarction: cardiovascular risk factors, medication use and lifestyle in Norwegian women and men. (29th July 2021) - Hopstock, L; Morseth, B; Cook, S; Eggen, AE; Grimgsgaard, S; Lundblad, MW; Lochen, ML; Mathiesen, EB; Nilsen, A; Njolstad, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Although the use of guidelines in clinical practice is emphasised, large multi-center studies of patients with cardiovascular disease have shown secondary prevention to be suboptimal, which increase the risk of recurrent events. Purpose: To examine ESC guideline treatment target achievement after myocardial infarction for cardiovascular risk factors, medication use and a broad range of lifestyle factors in women and men from a Norwegian general population. Methods: In a population-based study conducted 2015-2016 (65% attendance), 637 participants 40-95 years (23% women, 70% ≥65 years) had validated myocardial infarction. Cross-sectionally, we investigated target achievement for blood pressure (<140/90 mmHg, <130/80 mmHg if diabetes), LDL cholesterol (<1.8 mmol/L), HbA1c (<7.0% if diabetes), weight (body mass index (BMI) <25 kg/m2, waist circumference (women <80 cm, men <94 cm)), smoking (non-smoking), physical activity (self-reported >sedentary, accelerometer-measured moderate-to-vigorous ≥150 min/week), diet (intake of fruits ≥200 g/day, vegetables ≥200 g/day, fish ≥200 g/week, saturated fat <10E%, fiber ≥30g/day,   and alcohol (women ≤10 g/day, men ≤20 g/day)), and medication use (antihypertensives, lipid-lowering drugs, antithrombotics, antidiabetics) using regression models. Results: Proportion of target achievement was for blood pressure 55.8%, LDL cholesterol 9.3%, HbA1c 42.7%, BMI 19.5%, waist circumference 15.6%, non-smoking 86.2%, self-reported physical activity 79.5%, objectively measured physical activity 9.1%, intake of fruits 66.7%, vegetables 38.4%, fish 96.8%, saturated fat 25.4%, fiber 29.5%, and alcohol 78.5%, use of antidiabetics 84.3%, lipid-lowering drugs 86.8%, antihypertensives 78.5% and antithrombotics 77.9%. In total, 0.8% achieved all cardiovascular risk factor targets (blood pressure, LDL cholesterol, BMI and waist circumference combined). Compared to men, a lower proportion of women achieved the target for waist circumference (6.9% vs 18.1%, p = 0.002). Compared to participants 65 years or older, a higher proportion of those 40-64 years achieved the target for blood pressure (71.2% vs 49.0%, p < 0.001), and a lower proportion achieved the target for BMI (15.3 vs 21.4, p = 0.007). Conclusion: Secondary prevention after myocardial infarction was suboptimal in both women and men. A negligible proportion achieved the treatment target for all risk factors. Improvement in follow-up care after myocardial infarction is needed.